Factores de riesgo en atrofia musculo esquelética en adultos mayores que acuden al Centro Gerontológico de Babahoyo periodo noviembre 2023 – abril 2024. - Escobar Vera, Dixiana Jasmín (2024)
Skeletal muscle atrophy in the elderly represents a condition in which the person loses the functionality of one or more muscles, greatly affecting their quality of life. The main objective was to identify the risk factors associated with musculoskeletal atrophy in older adults between 65 and 80 years of age who attend the Babahoyo Gerontological Center. The methodology used was bibliographical in nature, with which reliable theoretical bases were compiled; descriptive, since the pathology was described, as well as the risk factors; deductive, due to the fact that it started from the effect to find the causes; and quantitative due to the representative population from which all the data of interest was collected. The results obtained showed a poor nutritional status, loss of muscle strength, insufficient physical activity, dependency, overweight, medium and low social level, non-communicable diseases such as high blood pressure (HTN) and osteoarthritis, and states of depression. It is concluded that the main risk factors for the development of skeletal muscle atrophy are age, nutritional status, muscle diseases, neurological pathologies and immobilization. The ages of greatest presence were 65 to 70 years, the social level of the study population was medium and low, there was a greater presence of the male sex, the diseases that presented in common were HTN and osteoarthritis. Finally, it was evident that the level of physical activity of the study population ranged from low to zero.